2019
DOI: 10.1109/access.2019.2953900
|View full text |Cite
|
Sign up to set email alerts
|

The State-of-the-Art of Human–Drone Interaction: A Survey

Abstract: Drones have expanded from military operations to performing a broad range of civilian applications. As drone usage increases, humans will interact with such systems more often, therefore, it is important to achieve a natural human-drone interaction. Although some knowledge can be derived from the field of human-robot interaction, drones can fly in a 3D space, which essentially changes how humans can interact with them, making human-drone interaction a field of its own. This paper is the first survey on the eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
1
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(65 citation statements)
references
References 68 publications
0
45
1
7
Order By: Relevance
“…The authors in [ 33 ] used the FCM method for six movements and did not indicate a success rate. In [ 42 ], 96.7% accuracy was achieved with 15 ms for six movements, while in our study, an average of 97% accuracy was achieved in 1.22 ms for 25 movements. In [ 35 ], a data set with 28800 data for 16 movements achieved 99% success in 67.6 ms, while our study achieved 98% accuracy in 10.8 ms with a data set featuring 49000 data for 25 movements.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…The authors in [ 33 ] used the FCM method for six movements and did not indicate a success rate. In [ 42 ], 96.7% accuracy was achieved with 15 ms for six movements, while in our study, an average of 97% accuracy was achieved in 1.22 ms for 25 movements. In [ 35 ], a data set with 28800 data for 16 movements achieved 99% success in 67.6 ms, while our study achieved 98% accuracy in 10.8 ms with a data set featuring 49000 data for 25 movements.…”
Section: Discussioncontrasting
confidence: 42%
“…Based on the literature review, the sensor types and methods used in their application are classified and shown in Table 1 . With the acceleration of research and development studies on UAVs, this technology has begun to be used in many new fields other than military and defense [ 42 ]. These developments have enabled UAVs to move towards human–UAV interactions, rather than environmental surveillance functions.…”
Section: Introductionmentioning
confidence: 99%
“…For this category of commercial-off-the-shelf sUAS, new innovative control interfaces have been recently developed. The emerging field of human–drone interaction (HDI) was surveyed by Tezza and Andujar [ 6 ], who discussed how HDI goes beyond control modalities, enhancing human interaction.…”
Section: Introductionmentioning
confidence: 99%
“…When considering the human operator, the key feature is to model the human being into the decision-making system [ 31 , 32 , 33 ]. A simple approach missing from other architectures in Table 1 would be to consider the skill level of the operator, and the time that the mission takes to be executed.…”
Section: Background and Related Workmentioning
confidence: 99%